Cytogenetics of four foam-nesting frog species of the Physalaemus gracilis group (Anura, Leptodactylidae) - Ferro, Juan M.; Taffarel, Alberto; Tomatis, Cristian; Borteiro, Claudio; Kolenc, Francisco; Gatto, Kaleb P. [UNESP]; Lourenço, Luciana B.; Baldo, Diego (FapUNIFESP (SciELO), 2022)
Intending to increase the knowledge about cytogenetics of Physalaemus and the sparsely studied P. gracilis group, we analyzed the karyotypes of P. carrizorum, P. gracilis, P. lisei, and P. sp. aff. gracilis. We studied chromosome morphology, heterochromatin patterns, Ag-NORs location and mapped the repetitive DNA sequence PcP190. All species showed diploid karyotypes composed of 22 bi-armed chromosomes and similar C- bands and Ag-NOR patterns. C-bands were mainly centromeric and pericentromeric; non-centromeric C-bands were detected on the telomeres of pair 1 in P. lisei, although polymorphic, and interstitially on pair 10 of P. gracilis. This last character is useful to distinguish P. gracilis from its sibling species P. sp. aff. gracilis. The Ag- NOR sites were detected on the long arms of chromosome pair 8 but with a variable position among species. Clusters of PcP190 showed centromeric and pericentromeric positions coincident with conspicuous C-bands, on pairs 2 and 9 in P. gracilis and P. sp. aff. gracilis, pair 3 in P. carrizorum, and pair 7 in P. lisei. These results significantly increase the knowledge about Physalaemus cytogenetics and encourage further studies on the satellite PcP190 in other genera of Leiuperinae to better understand its taxonomic distribution and the evolutionary dynamics.
Keywords: Ag-NORs; C-Bands; Leiuperinae; PcP190; satDNA